Javanese and Madurese Student's Dialects Interference in English Conversation - Syakur, Abd; Sudrajad, Wahyu (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2023)
This study was conducted based on the misperception’s students in different mother tongue when delivered conversation in English. The aim of this study is to know the interference dialects of mother tongue in English conversation The data was taken from observation field notes and video-audio recorder in junior high school in Pasuruan city because in this school include of differentiate of mother tongue (Javanese and Madurese) the data analysed uses qualitative methods. Then, the result of observation field notes displayed by narration. The data was transcriptions of the discussion and phonetics were analysed by Cambridge advanced dictionary. The data shows: Javanese students less accuracy when produced /æ, ɛə, i: eɪ, aʊ, ə:, ɔ:, u:, ɒ, ɪə, əʊ, ʊ, ɑ:, ɪ, ʊə, ɔɪ, aɪ/ but no interference in conversation process, the conversation still work. for the madurese speakers less accuracy when produced consonant, it sometimes made a lack when conducted conversation. The researcher found sometimes the Javanese speakers misplaced of the articulation when producing ‘F’ and ‘V’ changed by ‘P’.